Properties of stabilized recycled plastic concretes made with three types of cement - Shaikh, Faiz; Mali, Sarvesh (John Wiley and Sons Ltd., 2015)
The growing concern for the ready-mixed concrete industry is the disposal of returned unused concrete. In its plastic state, the concrete is a perishable product and the disposal of any unused concrete presents a set of challenges. An increase in environmental regulations requires the industry to implement the best practices that effectively reduce the quantity of by-product materials requiring disposal. This paper describes a preliminary experimental study on the effect of commercial stabilizer on the plastic and hardened properties of concretes made with three different types of cement commonly used in Australia, namely, general-purpose Portland cement (GP) (100 % ordinary Portland cement (OPC)), general-purpose blended (GB) cement (75 % OPC + 25 % class F fly ash (FA)) and low-heat (LH) cement (35 % OPC + 65 % blast-furnace slag). The effect of various stabilizer dosages on the efflux time (flow time) of GP, GB and LH cement grouts was studied in the initial phase. The results show that for a constant efflux time, the holding duration of the grouts increases with increasing stabilizer dosages (or amounts) and in the case of GB and LH cement grouts, the holding duration is longer than the GP cement grout for the same stabilizer dosage. In the next phase, the predicted stabilizer dosage was added to concretes made with the above three cements to evaluate the plastic and hardened properties of fresh concretes, stabilized concretes and blends of fresh concretes with 10, 25 and 50 % stabilized concretes. The results show that the initial slump values are within the tolerance, except they are higher when the stabilizer dosage is added after 1 h, but the final slump is within the tolerance of the control concrete. After stabilization of the concretes, the initial and final setting times of stabilized concretes increased to > 24 h. The initial and final setting times of the blended concrete containing fresh concrete and 10, 25 and 50 % stabilized concretes are similar to those of fresh concrete for all cement types. The stabilized concretes do not have any significant effect on the compressive strength and shrinkage compared with the control concrete.